Overview and update on the laboratory diagnosis of dermatophytosis - Shivaprakash M Rudramurthy; Dipika Shaw (Wolters Kluwer Medknow Publications, 2017)
Dermatophytosis, caused by dermatophytes is becoming difficult to treat due to various reasons. Accurate diagnosis is essential for the accurate management of this infection and prevention of relapse or recurrence. Although this condition is easy to diagnose clinically, due to overlapping signs and symptoms of few dermatological conditions it may be misdiagnosed necessitating laboratory confirmation. Isolation, identification of the dermatophytes and the antifungal susceptible profile may further help to initiate appropriate antifungal agent. The classical conventional techniques such as direct microscopic examination and isolation of fungi from the clinical specimens are still considered as an important modality of diagnosis. With the rise of the molecular era, molecular techniques are increasingly being applied to diagnose dermatophytosis and identify the dermatophytes. The present review provides an overview and update on the laboratory diagnosis of dermatophytosis.